2001
DOI: 10.1063/1.1413496
|View full text |Cite
|
Sign up to set email alerts
|

Resistivity of RMn12−xFex alloys

Abstract: The electrical resistivity of RMn 12Ϫx Fe x ͑RϭEr,Ho͒ polycrystalline system with xϭ0, 4, 5, and 6 was measured over the temperature range of 4 to 300 K. The resistivity increases sharply near the Ne ´el temperature T N for xϭ4, 5, and 6 which, according to existing theories, can be ascribed to the formation of superzone gaps. Then, the resistivity increase should be proportional to the staggered magnetization mЈ below T N , whereas we find experimentally that it is quadratic in mЈ. Thermal smearing of the gap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…These gaps reduce the effective number of conduction electrons below T N giving rise to the observed resistivity upturn [10]. On this basis we have explained the anomalous temperature variation of the resistivity of some RMn 12ÿx Fe x alloys studied earlier [11]. However, it has recently been found that the antiferromagnetic order in RMn 12ÿx Fe x alloys has the same symmetry as the crystalline lattice [12].…”
mentioning
confidence: 59%
“…These gaps reduce the effective number of conduction electrons below T N giving rise to the observed resistivity upturn [10]. On this basis we have explained the anomalous temperature variation of the resistivity of some RMn 12ÿx Fe x alloys studied earlier [11]. However, it has recently been found that the antiferromagnetic order in RMn 12ÿx Fe x alloys has the same symmetry as the crystalline lattice [12].…”
mentioning
confidence: 59%
“…At about 26 K a resistivity minimum appeared, followed by an upturn indicating an insulating behavior. Generally, the increase of resistivity below the AF ordering temperature is attributed to two factors [6]: One is carrier scattering by critical spin fluctuations; the other is the formation of an AF superzone gap, as a consequence of the additional periodicity of the AF state [7][8][9]. Considering that super-zone effects often occur at or just below T N or T AF-F(I) , while the resistivity of the present compound exhibits an increase before Néel order.…”
Section: Resultsmentioning
confidence: 73%
“…Consequently, complex magnetic behavior is expected to occur in the RMn 12−x T x solid solutions, due to competing ferro-and antiferromagnetic interactions. The magnetic and electrical properties of compounds with Fe as a transition element and with heavier rare earths have been reported in several publications ( [8][9][10][11][12][13][14][15][16][17] and references herein). Brief information concerning the selected Co compounds has been presented in [12,14], whereas a more systematic study of these intermetallics has been reported in [18,19].…”
Section: Introductionmentioning
confidence: 96%